Identiti seni bina Malaysia: Masalah dan penyelesaiannya - Kamarul Afizi Kosman,; Nik Lukman Nik Ibrahim, (Universiti Kebangsaan Malaysia, 2007)
One of the issues stressed by the government of Malaysia after independence was the establishment of national identity in various aspects of life. Architecture was one of them, and amongst the momentous tasks faced on that front was the adaptation of Malay architecture to modern design. Initial efforts proved fruitful and were executed with clear directions. However, at the beginning of 1980s, weaknesses surfaced, giving rise to problems of “balloon” and “cut-and-paste architecture”. One of the reasons for this was the narrow-mindedness amongst architectural professionals and academicians in interpreting the significance of architecture and the role it plays in the development of national identity. This state of affairs can be rectified in two ways. Firstly, in-depth studies of the tectonic elements and intrinsic values in Malay traditional architecture need to be done. Secondly, successful past efforts in establishing national identity at both national and international levels should be studied and understood. This article relates these issues to the “Arts and Crafts” movement that successfully helped to develop architectural identity in Britain in the early 19th century